2017
DOI: 10.3389/fmicb.2017.02389
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequencing of Mycobacterium bovis SP38 and Comparative Genomics of Mycobacterium bovis and M. tuberculosis Strains

Abstract: Mycobacterium bovis causes bovine tuberculosis and is the main organism responsible for zoonotic tuberculosis in humans. We performed the sequencing, assembly and annotation of a Brazilian strain of M. bovis named SP38, and performed comparative genomics of M. bovis genomes deposited in GenBank. M. bovis SP38 has a traditional tuberculous mycobacterium genome of 4,347,648 bp, with 65.5% GC, and 4,216 genes. The majority of CDSs (2,805, 69.3%) have predictive function, while 1,206 (30.07%) are hypothetical. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 93 publications
4
46
0
7
Order By: Relevance
“…There were only three M. bovis genomes without CC classification isolated from humans in Germany that appeared closely related to genomes of the CC Eu2 (Figure 2 - indicated as **, part of isolates also emerging from node C). The CC Eu2 has been described as dominant in the Iberian Peninsula and also detected in other countries of Europe and in Brazil (Rodriguez-Campos et al, 2012; Zimpel et al, 2017a). Its actual worldwide occurrence, however, is unknown.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…There were only three M. bovis genomes without CC classification isolated from humans in Germany that appeared closely related to genomes of the CC Eu2 (Figure 2 - indicated as **, part of isolates also emerging from node C). The CC Eu2 has been described as dominant in the Iberian Peninsula and also detected in other countries of Europe and in Brazil (Rodriguez-Campos et al, 2012; Zimpel et al, 2017a). Its actual worldwide occurrence, however, is unknown.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, attained results suggest that M. bovis strains are likely to cluster based on geographical location (Dippenaar et al, 2017; Kraemer Zimpel et al, 2017; Lasserre et al, 2018). In our previous study, we have also shown that few M. bovis genomes do not carry any CC genetic marker (Zimpel et al, 2017a), a phenomenon that was recently observed in M. bovis isolates from one cattle herd in the USA and from slaughterhouse cattle in Eritrea (Ghebremariam et al, 2018; Orloski et al, 2018b). These findings suggest that CCs are unlikely to represent the whole diversity of M. bovis strains, warranting further evaluation of M. bovis molecular lineages (Zimpel et al, 2017a; Lasserre et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations